Inversions of service-dominant logic. (September 2014) - Vargo, Stephen L.; Lusch, Robert F.
Value creation, both its nature and scope, can be better and more accurately understood by inverting six characteristics of goods-dominant logic, or what is also known as "old enterprise logic" or "neoclassical economics, " into a service-dominant-informed perspective. These six inversions include (1) entrepreneurship and the view that value creation is an unfolding, emergent process seen as superordinate to management, (2) effectual processes understood as primary in relation to predictive processes and better for informing actors about the interactive, resource-integrating, collaborate nature of value creation, (3) marketing being fundamental to value creation and taking primacy over manufacturing, (4) innovation as more fundamental to, and descriptive of, value creation than invention, (5) a focus on effectiveness as captured by value in use and value in context for beneficial actors taking precedence over efficiency, which is inherently a firm-centric lens, and finally (6) the the predominant reliance on heuristics rather than rational, calculative decision making.